3D Coaxial Printing of Small‐Diameter Artificial Arteries - Yuxiang Zhu; Siying Liu; Xuan Mei; Zeng Lin; Tiffany V. Pulido; Jixin Hou; Srikar Anudeep Remani; Dhanush Patil; Martin Taylor Sobczak; Arunachalam Ramanathan; Sri Vaishnavi Thummalapalli; Lindsay B. Chambers; et al. (Small Structures)
As a treatment for the widely spread cardiovascular diseases (CVD), bypass vascular grafts have room for improvement in terms of mechanical property match with native arteries. A 3D‐printed nozzle is presented, featuring unique internal structures, to extrude artificial vascular grafts with a flower‐mimicking geometry. The multilayer‐structured graft wall allows the inner and outer layers to interfere sequentially during lateral expansion, replicating the nonlinear elasticity of native vessels. Both experiment and simulation results verify the necessity and benefit of the flower‐mimicking structure in obtaining the self‐toughening behavior. The gelation study of natural polymers and the utilization of sacrificial phase enables the smooth extrusion of the multiphase conduit, where computer‐assisted image analysis is employed to quantify manufacturing fidelity. The cell viability tests demonstrate the cytocompatibility of the gelatin methacryloyl (GelMA)/sodium alginate grafts, suggesting potential for further clinical research with further developments. This study presents a feasible approach for fabricating bypass vascular grafts and inspires future treatments for CVD.